Raman scattering study of the PbZr1-xTixO3 system: Rhombohedral-monoclinic-tetragonal phase transitions - Souza Filho, A. G.; Lima, K. C. V.; Ayala, A. P.; Guedes, I.; Freire, P. T. C.; Melo, F. E. A.; Mendes Filho, J.; Araújo, E. B. [UNESP]; Eiras, J. A. (American Physical Society (APS), 2002)
In this paper we present a Raman-scattering study of the phase transitions in the PbZr1-xTixO3 systems around the morphotropic phase boundary over a wide temperature range. The boundary between rhombohedral and monoclinic phases was found to be a quasivertical line between x = 0.46 and x = 0.47. We also studied the monoclinic-tetragonal phase boundary and our spectroscopic results agree very well with those reported by using x-ray diffraction.
Keywords: lead; oxygen; titanium; zirconium; geometry; phase transition; radiation scattering; Raman spectrometry; temperature; X ray diffraction